Effect of caffeine and caffeine cessation on cerebrovascular reactivity in patients with migraine. Issue 2 (3rd February 2022) - Gil, Young‐Eun; Lee, Mi Ji; Cho, Soohyun; Chung, Chin‐Sang
Abstract: Objective: To investigate the effect of chronic caffeine use and caffeine cessation on vasodilatory function in the posterior circulation in patients with migraine. Background: Studies regarding cerebrovascular reactivity (CVR) using vasodilatory stimuli in patients with migraine have yielded conflicting results. We postulated that CVR may not be static, and caffeine might negatively affect vasodilatory function via its vasoconstrictive effect. Methods: In this prospective longitudinal observation study, we recruited patients with episodic migraine who were 18–50 years of age and free of vascular risk factors at the Samsung Medical Center between August 2015 and March 2020. Patients were classified into caffeine users and non‐users at baseline, and caffeine users were instructed to discontinue caffeine intake. We measured the mean breath‐holding index (BHI) of bilateral posterior cerebral arteries (PCA) using transcranial Doppler in all the included patients at baseline and followed up after 3 months. We compared breath‐holding indices cross‐sectionally between caffeine users and non‐users and analyzed BHI changes according to caffeine cessation. Results: In total, 84 patients completed the study protocol. Cross‐sectional analysis showed that the baseline BHI of PCA was lower in caffeine users ( n  = 56, 1.1 [interquartile range (IQR) 0.8–1.3]) than that in nonusers ( n  = 28, 1.3 [IQR 1.0–1.5], p  = 0.030). In the longitudinal analysis, caffeine quitters showed a significant improvement in BHI in PCA (baseline 1.1 [IQR 0.8–1.2], follow‐up 1.3 [IQR 1.0–1.4], p  = 0.034), whereas continuous users and non‐users did not. Multivariable analysis showed an independent effect of caffeine cessation on the changes in BHI of PCA (unstandardized β  = 0.27, 95% confidence interval 0.01–0.53, p  = 0.044). Conclusion: In patients with migraine, caffeine use is associated with reduced CVR in the posterior circulation, and caffeine cessation might be beneficial in improving CVR.